Duration of smoking cessation for the prevention of surgical wound healing complications - Barbara Vieira Cavichio; Daniele Alcalá Pompeo; Graziella Allana Serra Alves de Oliveira Oller; Lídia Aparecida Rossi (SciELO, 2014)
The study aimed to find scientific evidence about the duration of preoperative smoking cessation required to reduce surgical wound healing complications. An integrative review was performed in the databases, Latin American and Caribbean Literature on Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE), from 08/17/2012 to 09/17/2012, using the keywords: tobacco use cessation and wound healing; tobacco use cessation and preoperative period; tobacco use cessation and perioperative period (LILACS) and tobacco use cessation and perioperative period; tobacco use cessation and wound healing (MEDLINE). Out of the 81 eligible studies, 12 were included. The duration of smoking cessation needed to reduce healing complications was at least four weeks (four studies with level of evidence I, three studies with level of evidence II, two studies with level of evidence IV, and one study with level of evidence VII).